Strategic Orientation, Culture, and Commitment Toward Institutional Performance of Independent Palm Oil Farmers - Fanisa Salsabilla Lubis; Nurliza; Shenny Oktoriana (Jurnal Ilmu Pertanian Indonesia, 2025)
Independent oil palm farmers are crucial to the growth of the national economy. However, due to subpar institutional and farmer group performance, independent oil palm farmers' productivity still needs to improve. This research aimed to maximize institutional performance within the frameworks of social exchange theory and resource-based view theory. The study employed structural equation modeling, or SMART-PLS, and quantitative descriptive methodologies to examine 92 farmer group administrators in Sambas Regency, West Kalimantan. The study's findings illustrate that strategic orientation, culture, and commitment affect institutional/farmer group performance. In maximizing institutional performance, the following was done: 1) planning for environmental conservation by setting clear deadlines and assigning members to consider environmental sustainability and refrain from burning land; 2) communicating with the community and members to foster community harmony; 3) holding online group discussions for members who are unable to attend in order to save time discussing issues collectively; b. imposing strict sanctions for infractions by its members; 4) fostering active dialogues among members and working directly or virtually with instructors regarding oil palm cultivation knowledge. The most recent study aims to develop strategies for enhancing institutional and farmer group performance through strategic orientation, culture, and commitment. Keywords: farmer group, performance, independent oil palm farmers, SMART-PLS